2020
DOI: 10.7717/peerj.10212
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and social functioning in people with borderline personality disorder and their first-degree relatives

Abstract: Background A few papers studying healthy, first-degree relatives of people with borderline personality disorder (BPD) have found that this group presents attention and memory problems. However, current research has not analyzed their social cognition. Materials and Methods We designed an age-, gender- and education-level matched case-control study involving 57 people with BPD, 32 of their first-degree relatives, and 57 healthy controls in Spain in 2018–2019. All were assessed for social cognition and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, two studies have analyzed social cognition in first-degree relatives of patients with BPD [ 23 , 45 ], and none used the MASC subscales to assess ToM through the interpretation of emotions, thoughts and intentions. This classification is particularly relevant, with direct implications for the analysis of patients’ relational styles, the most suitable marker for the diagnosis of BPD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, two studies have analyzed social cognition in first-degree relatives of patients with BPD [ 23 , 45 ], and none used the MASC subscales to assess ToM through the interpretation of emotions, thoughts and intentions. This classification is particularly relevant, with direct implications for the analysis of patients’ relational styles, the most suitable marker for the diagnosis of BPD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical power was calculated using the previous work of Ortega-Díaz et al [ 23 ] in which different variables were collected for the study using unbalanced one-way analysis of variance (ANOVA) for the BPD patient ( n = 57), relative ( n = 32) and control ( n = 57) groups. The effect sizes were calculated for the three subscores (emotions, intentions and thoughts).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study 22 found that the close relatives of individuals with BPD exhibit some signs of the difficulties in social cognition and interaction that are characteristic of individuals with BPD. This is relevant to attempts to better understand the aetiology, and hence also the treatment, of BPD.…”
Section: The Family Contextmentioning
confidence: 99%